Model Kampanye Digital Sinergis Berbasis Moderasi Beragama dan Kearifan Lokal di Desa Betara Kanan Kabupaten Tanjung Jabung Barat - Rahmawati, Azizah; Ehwan, Munir; Ramadhaniati, Fajria; Rahmana, Satria; Binarwan, M. Irfan; Rusmita, Rusmita; Imanda, Amalia; Zafira, Rachmawati; Silpani, Maya; Hardiyani, Sri; Ramadhan, M. Zakki; Nida, Khairun; Putri, Sela Adelia; Setyawan, Dito; Herawati, Zainab Rizky; Rahman, Aulia; Muzdalifah, Muzdalifah; Rahmah, Aulia; Afryza, Nur (Civiliza Publishing, 2025)
Strengthening social harmony in the midst of a pluralistic village community is a challenge in the digital era. This article aims to describe a synergistic digital campaign model based on religious moderation and local wisdom applied in Betara Kanan Village, West Tanjung Jabung Regency. This activity is part of the collaborative Real Work Lecture (Kukerta) program across study programs involving students of Islamic Religious Education, Islamic Communication and Broadcasting, Islamic Family Law, Constitutional Law, Sharia Economics, and Sharia Business Management. The implementation method uses the Participatory Action Research (PAR) approach through the stages of observation, planning, implementation, and evaluation. The results of the activity show a significant increase in literacy, religious moderation and digital ethics of the community, strengthening digital legal awareness, and empowering the sharia economy through the legality of MSMEs, halal certificates, and digital marketing. This model has novelty in cross-disciplinary collaboration and the use of digital media as a value-based social education instrument. Practically, this campaign model can be replicated as a strategy to strengthen village social harmony based on digital and local wisdom.